Gene Therapy for Inherited Bleeding Disorders - Arruda, Valder R.; Weber, Jesse; Samelson-Jones, Benjamin J. (Seminars in Thrombosis and Hemostasis, 2021)
Decades of preclinical and clinical studies developing gene therapy for hemophilia are poised to bear fruit with current promising pivotal studies likely to lead to regulatory approval. However, this recent success should not obscure the multiple challenges that were overcome to reach this destination. Gene therapy for hemophilia A and B benefited from advancements in the general gene therapy field, such as the development of adeno-associated viral vectors, as well as disease-specific breakthroughs, like the identification of B-domain deleted factor VIII and hyperactive factor IX Padua. The gene therapy field has also benefited from hemophilia B clinical studies, which revealed for the first time critical safety concerns related to immune responses to the vector capsid not anticipated in preclinical models. Preclinical studies have also investigated gene transfer approaches for other rare inherited bleeding disorders, including factor VII deficiency, von Willebrand disease, and Glanzmann thrombasthenia. Here we review the successful gene therapy journey for hemophilia and pose some unanswered questions. We then discuss the current state of gene therapy for these other rare inherited bleeding disorders and how the lessons of hemophilia gene therapy may guide clinical development.
Keywords: gene therapy; hemophilia; inherited bleeding disorders; AAV; lentiviral; factor IX; factor VIII